ANALISIS ARCHITECTURE TEKNOLOGI MENGGUNAKAN SABSA UNTUK MENINGKATKAN KEAMANAN DI RUMAH SAKIT QUEEN LATIFA - Alvian Trias Kurniawan Alvian; Bambang Soedijono WA; Asro Nasiri (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2022)
Widespread use of Internet and increasing reliance on public packet-switched networks for e-commerce, telecommuting etc., has resulted in an increase in malicious attacks on security & malware in enterprises. Businesses in the healthcare sector use health information networks and information technology that work together to improve patient safety, increase treatment effectiveness, and increase efficiency. The purpose of this study is to address security and privacy concerns with integrated healthcare or medical records businesses. The security system implemented in several hospitals requires periodic improvements and reviews for the comfort and safety of the hospital and the patient. The use of the SABSA framework in this study focuses on IT security that can be applied in various industrial and organizational sectors as an EISA development. This paper discusses analyzing and improving EISA through synergistic integration of information security architecture into EA to improve data and information security. For its implementation using the TOGAF framework for Enterprise Architecture, while for information security architecture it will use the SABSA framework.